Modern vehicles for regional railways - Josef Kolář (Acta Polytechnica CTU Proceedings)
The paper analyses the history of two-axle rail vehicles (rail buses) used for operation on regional lines in Czechoslovakia. It also shows trends in the development of modern light autonomous rolling stocks usable for passenger transport on unprofitable regional lines in Western Europe. The measures adopted in the transport policy of the Czech Republic for the period 2021–2027 for regional railway vehicles in the Czech Republic are presented. The final part of the paper presents the results of study of the concepts of a two-axle hybrid and electric rail buses and a conceptual design of a modular solution of a partially low-floor vehicle BEMU and HEMU for passenger regional rail transport. This paper shows that it is very problematic to create a light rail vehicle (LVR) that will be economical and environmentally friendly for regional transport and at the same time will meet the requirements of standards ČSN EN 12 663, category P2 and ČSN EN 15 227, category C I and will be friendly to road users.